Detection of Sibutramine and Fluoxetine Adulteration in Unregistered Weight-Loss Supplement Products Containing Natural Extracts Sold in Four Provinces of Lao PDR - her, chithdavone (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The adulteration of unregistered weight-loss supplements marketed as natural products with undisclosed pharmaceutical substances is a significant public health concern. Sibutramine is an anti-obesity drug and withdrawn from the market due to associated cardiovascular risks and fluoxetine, selective serotonin reuptake inhibitors are among the most commonly reported adulterants. Their undeclared presence, particularly when combined, poses serious risks to consumer health. This study aimed to determine the presence and quantity of sibutramine and fluoxetine in unregistered weight-loss supplements using a validated High-Performance Liquid Chromatography with Ultraviolet Detection (HPLC-UV) method. An HPLC-UV method for the determination of sibutramine and fluoxetine were developed and validated. A total of 100 samples of unregistered weight-loss supplements containing natural extracts were collected from markets and retail stores across four provinces of Lao PDR. Samples were analyzed by HPLC-UV at a detection wavelength of 224 nm. The method shown excellent linearity (R² > 0.999) in a concentration range of 5-100 µg/mL. Limits of detection were 0.18 µg/mL for sibutramine and 0.19 µg/mL for fluoxetine, while limits of quantification were 0.55 µg/mL and 0.59 µg/mL, respectively. Accuracy ranged from 97.38% to 99.32%, with precision (%RSD) below 2%. Sibutramine was detected in 10% of samples (32.1-245.9 µg/g), fluoxetine in 15% (36.6-380.9 µg/g), and both compounds were detected together in 3% of samples. Adulterated unregistered weight-loss supplements were found across all surveyed regions. In conclusion, these findings confirm the presence of undeclared pharmaceutical adulterants in unregistered weight-loss supplements and highlight the need for stronger regulatory oversight, enhanced market monitoring, and greater public awareness to prevent the sale of unregistered products and reduce the associated health risks.